Environmental causes of obesity: sociocultural, built environment and economic factors - Kumanyika, Shiriki (Henry Stewart Talks, 2007)
Rapid increases in obesity prevalence globally, Increases in obesity among immigrants, Socio-cultural influences: human relationships and interactions, attitudes, norms and values and social structure, "Built environment" influences: how land and space are organised and used and the infrastructure for getting from place to place, Economic influences: determinants of food access and availability and physical activity patterns, Variations in obesity prevalence globally and in Europe, Africa and America, Societal transformations, Shifts in dietary patterns, Shifts in physical activity, The most important environmental pathways: media environment and media use, food marketing, options for physical activity and individual socio-cultural perspectives